Exogenous application of salicylic acid regulates antioxidant enzyme activities and quality attributes of Umran ber (Ziziphus mauritiana) fruits under cold storage - SHARMA, ANIL; BONS, HARSIMRAT KAUR (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out to observe the influence of pre-harvest application of salicylic acid (1, 2 and 3 mM) on shelf life and quality attributes of ber fruits cv. Umran (Ziziphus mauritiana Lamk.) under cold storage conditions (7.5±10C and 90–95% RH). The cold-stored fruits were assessed for various physico-chemical attributes and enzymatic activities at 7 days interval up to 28 days of storage. Above study revealed that fruits treated with salicylic acid @3 mM resulted in reduced physiological loss in fruit weight, spoilage and increased firmness, soluble solids content, antioxidant activity and carotenoids. Furthermore, it suppressed activities of cell wall degrading enzymes like PG, PPO, PME and increased the activity of superoxide dismutase peroxidase and catalase enzymes. It was concluded that pre-harvest spray of salicylic acid @3 mM was more effective in regulating enzymatic activities, thereby improving quality attributes and shelf life of ber fruits up to 21 days at cold storage.